Total Synthesis of 5-Hydroxygoniothalamin - Patpi, Santhosh Reddy; Jin, Guangyi; Kantevari, Srinivas (Synthesis, 2019)
The total synthesis of 5-hydroxygoniothalamin is achieved from commercially available l-xylose. The α,β-unsaturated-δ-lactone core is constructed in very good yield by utilizing one-carbon and two-carbon cis-Wittig olefinations and δ-lactonization using Yamaguchi conditions. Subsequent Grubbs cross-metathesis followed by desilylation results in 5-hydroxygoniothalamin.
Keywords: C1 Wittig reaction; C2 Wittig reaction; Yamaguchi reaction; cross-metathesis; 5-hydroxygoniothalamin